PWE-167 The influence of a simple blood transfusion policy on over-transfusion in acute upper gastro-intestinal haemorrhage. (22nd June 2015) - Stokes, A; Thompson, C; Clegg, A; Snook, J
Abstract : Introduction: Acute upper gastro-intestinal haemorrhage (AUGIH) is a common medical emergency. Whilst frequently treated with blood transfusion, RCT evidence suggests that a restrictive transfusion policy can reduce the risk of re-bleeding and death. Yet previous audits have shown a high prevalence of over-transfusion - a situation where blood is administered in excess of requirements, with the potential for deleterious effects. This study describes the impact of a simple blood transfusion policy to address over-transfusion in AUGIH. Method: A cross-match policy was devised (see Table 1 ) to limit the number of units initially provided for patients with AUGIH according to the pre-transfusion haemoglobin concentration ([Hb]) and presence of shock and/or suspected varices. The proposed target post-transfusion [Hb] was 90–100g/l. Anonymised data was collected for all patients with suspected AUGIH during two six-month periods, before (Group 1) and after (Group 2) introduction of the policy. Over-transfusion was arbitrarily defined as a post-transfusion [Hb] exceeding 100 g/l. Results: Group 1 (n = 122) and Group 2 (n = 105) were comparable in terms of age, sex, [Hb] at presentation and Rockall score. The proportion of patients over-transfused decreased from 48% in Group 1 to 28% in Group 2 (OR 0.43; 95% CI 0.19–0.98). Logistic regression analysis of combined data from the two cohorts confirmed that "initial [Hb]" and "units transfused" were the two major independent predictors of over-transfusion. The respective total blood usage figures for Groups 1 and 2 were 259 v 148 units cross-matched (a 43% reduction), and 198 v 127 units transfused in (a 36% reduction). Contributors to the latter were (1) a reduction in the proportion of patients transfused (58% v 50%; χ 2 =1.36, p = 0.24), and (2) a reduction in the number of units administered to each recipient (mean 2.8 v 2.4; t test 1.95, p = 0.05). Conclusion: Over-transfusion in AUGIH is common and can be substantially reduced by the introduction of a simple cross-match policy. Direct benefits include a reduction in blood usage – our figures indicate a drop from 162 to 121 units per 100 patients with AUGIH. A typical DGH managing 250 cases a year could therefore potentially save £12, 000 pa on blood alone – if applied across the NHS in England this equates to over £2 million pa. Further potential benefits might include reduced morbidity and mortality, and indirect cost savings from a reduction in the interventions and extended lengths of stay for rebleeding episodes. Disclosure of interest: None Declared.